Une méthodologie générale pour l’étude numérique du couplage fluide-structure par une approche multicode - Mouronval, Anne-Sophie; Hadjadj, Abdellah; Lefrançois, Emmanuel (European Journal of Computational Mechanics, 2003)
This paper describes the development of a numerical tool that is needed to investigate fluid/structure interactions occurring in overexpanded rocket nozzles. A simple methodology is proposed in order to adapt to fluid/structure coupling existing codes dedicated to fluid mechanics and structural mechanics. We survey numerical methods for moving boundaries problems, pay special attention to methods using dynamic meshes and underline several technical difficulties that are specific to fluid/structure interactions problems. Finally, we combine the fluid and structural solvers using the most popular staggered procedure. The resulting code is validated by computing supersonic panel flutter. Some conclusions are drawn concerning the type of numerical schemes (for fluid solvers) that should be used for this application.